President Joko Widodo's Leadership Style Model in Controlling Covid-19 - Muhammad Reza Fahlevy; Muhammad Noor; I Ketut Gunawan; Amera Mahfin (Journal of Local Government Issues (LOGOS), 2022)
During the current COVID-19 pandemic, many state leaders must make decisions quickly. Quick decision-making also has a positive impact on society and the country. Leadership style greatly influences a president in managing a pandemic. As head of state, the President can use his executive power to solve problems, especially pressing ones. This study aims to examine the model of the President's leadership style in dealing with the COVID-19 pandemic in Indonesia. In addition, this model will be the basis for forming a particular program that focuses on developing leadership competencies and being an evaluation in urgent situations. This type of research is qualitative. The data used in this study is a literature study that focuses on using secondary data in the form of forty news media articles taken from March 2, 2020, to October 2020. The analysis of news media data was managed using Nvivo 12 Plus software through coding and cross-tabulation analysis. The results of this study are the model of President Joko Widodo's leadership style, applying various leadership styles in controlling the COVID-19 pandemic in Indonesia. This study concludes that the leadership style is inefficient in handling the COVID-19 pandemic, even though President Joko Widodo has directly taken over the handling of the crisis.